(untitled) (Tanzania Medical Journal, 2022)
Background The practice of unhygienic defecation in an open spaces other than toilets is what is termed as open defecation. One of the reasons for poor hygiene in Nigeria is open defecation. Assessing the knowledge of people assesses the general understanding of a community on a particular topic under study, whereas the attitude component assesses the feeling and cultural beliefs toward the topic. To ensure an open defecation free environment, more attention should be towards changing the attitudes of the community toward OD, not only building latrines. Broad objective This study assessed the factors associated with open defecation as well as Knowledge, Attitude, and Practice in a rural community of Sule Tankarkar Local Government of Jigawa State. Methodology This cross sectional study was a community based that recruited 160 participants using multistage sampling techniques. A questionnaire was interview administered to the participant. Data was analyzed using frequency, percentage, mean, standard deviation and chi-square in SPSS version 20 at alpha level of 0.05. Results The majority of the participants were male 132 (82.5%) within the age range of 29-39 49(30.6%) with only primary education were 33.8 %. The majority 158 (98.7%) households possessed latrines in their houses. Majority of the participants, 133 (83.1%), possessed a good knowledge of negative effects of open defecation. However, two-third of the participants had a negative attitude (66.9%) and poor practice (36.3%) towards ending open defecation. Conclusion and recommendation Latrines were found to be present in almost all the households which participated in this study. Factors associated with latrine ownership were government policy, the type of soil, poverty, and educational level. Good Knowledge on open defecation was seen among the participants but possess negative attitudes and poor practice of latrine usage. Therefore, there is need for empowerments to construct very good latrine with less cost in order to improve on the current practice to end open defection.